2014
DOI: 10.5217/ir.2014.12.4.275
|View full text |Cite
|
Sign up to set email alerts
|

Would You Recommend Screening Colonoscopy for the Very Elderly?

Abstract: Life expectancy in Korea has increased, and the number of screening colonoscopies in the elderly has also dramatically increased. The net benefit of colonoscopy in the very elderly (≥80 years of age as defined by the World Health Organization) may be reduced because of the competing risk of mortality due to other diseases. Therefore, the decision to perform screening colonoscopy may be more complex in this age group. As the potential increase in life expectancy due to screening colonoscopy is significantly red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…This may occur due to slowed bowel motility, previous surgeries and other comorbidities, a high rate of constipation, poor adherence, and misunderstanding of the preparation instructions. Some authors recommend that older patients undergo pre-procedure consultations for evaluation, and that an individualized approach is used to improve preparation rates (6) . Another parameter recommended by ASGE as a quality criterion is a cecal intubation rate greater than 95; in the study population, the rate found was 100%.…”
Section: Discussionmentioning
confidence: 99%
“…This may occur due to slowed bowel motility, previous surgeries and other comorbidities, a high rate of constipation, poor adherence, and misunderstanding of the preparation instructions. Some authors recommend that older patients undergo pre-procedure consultations for evaluation, and that an individualized approach is used to improve preparation rates (6) . Another parameter recommended by ASGE as a quality criterion is a cecal intubation rate greater than 95; in the study population, the rate found was 100%.…”
Section: Discussionmentioning
confidence: 99%
“…Life expectancy has increased worldwide; accordingly, the number of screening colonoscopies performed in elderly patients has dramatically increased [1,2] . As the incidence of colorectal cancer increases with age, colonoscopy plays a major role in the detection of CRCs in elderly patients [1,2] .…”
Section: Introductionmentioning
confidence: 99%
“…As the incidence of colorectal cancer increases with age, colonoscopy plays a major role in the detection of CRCs in elderly patients [1,2] . Although the yield of colonoscopy in elderly patients is high, colonoscopy in this population is often difficult because of higher rates of adverse events and noncompliance than in younger patients.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the incidence of CRC is rapidly increasing, especially in Asian countries including Korea [2][3][4][5]. The substantial interest in identifying potentially modifiable risk factors, such as cigarette smoking, diabetes, hyperlipidemia, and obesity, have kept pace with the increase in incidence of CRC.…”
Section: Introductionmentioning
confidence: 99%